A 'popular option' for development? Reconsidering the rise and fall of Chile's political economy of socialism. (1st June 2021) - Frens-String, Joshua
Abstract : As Salvador Allende and his supporters forged a democratic path towards socialism, the task of building a more sovereign and egalitarian national economy became one of the Popular Unity (UP) revolution's first priorities. To that end, Allende's coalition promoted a massive downward redistribution of income during its first months in office while also extending state control over many of the country's most essential industries. Chile's food economy, including its agricultural sector, received special attention during this early period as both purchasing power and domestic production soared. However, when a combination of economic, ecological and political factors caused consumer production to stagnate, acute shortages for a wide range of goods raised questions about the viability of the UP's plans for a more just consumer economy. The emergence of a powerful opposition movement also raised questions about the government's reluctance to pursue substantive political changes at the same time that it implemented major economic reforms. By examining the political economy of the UP experiment in the context of Chile's 2019–20 uprising against inequality and political exclusion, this article reconsiders the consequences of the UP's inability to link economic transformations with changes in how political power was exercised in mid-century Chile.